Kinerja Bank Syariah Indonesia Tahun 2021 Dengan Pendekatan Islamicity Performance Index - Arisandi, Debby; Diandra, Didip; Juliansyah, Shi Badio Muhammad (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2023)
The aim of this research is to find out and explain the performance of Bank Syariah Indonesia (BSI) in 2021 using the Islamicity Performance Index approach using a quantitative descriptive type of research. The sample in this study is Indonesian Sharia Banks listed on the Indonesia Stock Exchange (IDX) in 2021. The data source used is secondary data and data collection techniques use literature searches. Data analysis techniques using non-statistical quantitative methods descriptive quantitative methods. In the Islamicity Performance Index indicators, the performance of Bank Syariah Indonesia is as follows: Profit Sharing Ratio (PSR) results of the analysis are in very good predicate, Zakat Performance Index (ZPR) is in bad predicate, Equitable Distribution Ratio (EDR) which includes Qardh and Donation is not good, Employee Expense is not good, and Net Profit is not good, Islamic Investment vs. Non-Islamic Investment Ratio is very good, and Islamic Income vs. Non-Islamic Income Ratio is very good. Thus, the results of the performance of Bank Syariah Indonesia (BSI) for the 2021 period using the Islamicity Performance Index approach, the performance of Bank Syariah Indonesia has obtained results that are in accordance with using this method.